Pre-history and origins of the hero in El libro del cavallero Zifar and Amadís de Gaula - Axayácatl Campos García Rojas (Medievalia, 2018)
This article studies the concept of pre-historyin the heroic and chivalric development of the main characters in El libro del Cavallero Zifar and Amadís de Gaula. In the narrative of this romances, the pre-history refers to the account of significant events prior to the gestation of the hero, and to the previous history of his origins. The analysis of the works and its structure allows us to understand two types of pre-history: One built with remote, mythical and legendary elements, brought to the knight’s present life as memories given by his ancestors; and the other given to the reader as part of the narrative and plot of the work; this one results more direct and closer in time.